The effects of weighted skates on ice-skating kinematics, kinetics and muscular activity - Mavor, M. P.; Hay, D. C.; Graham, R. B. (Journal of Sports Sciences, 2018)
Sport-specific resistance training, through limb loading, can be a complimentary training method to traditional resistance training by loading the working muscles during all phases of a specific movement. The purpose of this study was to examine the acute effects of skating with an additional load on the skate, using a skate weight prototype, on kinematics, kinetics, and muscle activation during the acceleration phase while skating on a synthetic ice surface. 10 male hockey skaters accelerated from rest (standing erect with knees slightly bent) under four non-randomized load conditions: baseline 1 (no weight), light (0.9 kg per skate), heavy (1.8 kg per skate), and baseline 2 (no weight). Skating with additional weight caused athletes to skate slower (p < 0.001; ?2 = 0.551), and led to few changes in kinematics: hip sagittal range of motion (ROM) decreased (2.2°; p = 0.032; Eta2 = 0.274), hip transverse ROM decreased (3.4°; p < 0.001; Eta2 = 0.494), ankle sagittal ROM decreased (2.3°; p = 0.022; Eta2 = 0.295), and knee sagittal ROM increased (7.8°; p < 0.001, Eta2 = 0.761). Overall, weighted skates decreased skating velocity, but athletes maintained similar muscle activation profiles (magnitude and trends) with minor changes to their skating kinematics.